Bidirectional shake table testing of RC columns retrofitted and repaired with shape memory alloy spirals. (1st April 2018) - Jung, Donghyuk; Wilcoski, James; Andrawes, Bassem
Highlights: This study aims to examine the capability and feasibility of the active confinement technique using SMA spirals to enhance seismic performance of RC columns with insufficient flexural ductility. An in-depth understanding of the realistic seismic responses of SMA confined RC columns is provided through bi-directional shake table tests. The SMA repair procedure for damaged RC columns are rapidly demonstrated and its efficacy is experimentally proved under sequential seismic excitations. Abstract: Under the extreme threats of strong earthquakes, bridge columns are required to remain functional to ensure the safety and structural integrity of the entire bridge system. However, many existing bridges designed according to old seismic design provisions lack flexural ductility due to insufficient concrete confinement. Lack of confinement in old bridges is often addressed through providing supplementary external passive confinement. Recently, an active confinement technique using Shape Memory Alloys (SMAs) has been proposed as a more effective alternative to conventional passive confinement methods. In this study, the application of SMA confinement in seismic retrofitting and emergency repair of RC bridge columns is examined experimentally through a series of shake table tests. Two 1/6-scale RC columns, retrofitted and repaired with SMA spirals, are tested simultaneously under bidirectional test motions with varying intensity. Test results show that SMA confinement is highly effective in mitigating the seismic damage and improving the seismic performance of retrofitted and repaired RC columns subjected to strong earthquakes.